SUKSIS - Full start to becoming a cop - The Star, (2009)
Public University students who have completed their Undergraduate Police Volunteer Corps (Suksis) module can now be immediately absorbed into the Police Volunteer Reserve (PVR), says Inspector-General of Police Tan Sri Musa Hassan.